Image_3_Investigating Controls on the Formation and Distribution of Wintertime Storage of Water in Supraglacial Lakes.JPEG - Derrick Julius Lampkin; Lora Koenig; Casey Joseph; Jason Eric Box (2020)
Supraglacial lakes over the Greenland Ice Sheet can demonstrate multi-model drainage states. Lakes can demonstrate incomplete drainage, where residual melt can become buried under ice and snow and survive throughout the winter. We evaluate atmospheric factors that influence the propensity for the formation of buried lakes over the ice sheet. We examine the spatial and temporal occurrence and behavior of buried lakes over the Jakobshavn Isbrae and Zachariae Isstrøm outlet basins and assess the magnitude of insolation necessary to preserve melt water using a numerical lake model from 2009 to 2012. Buried lakes tend to occur at higher elevations within the ablation zone and those present at elevations > 1000 m tend to reoccur over several seasons. Lakes without buried water are relatively small (∼1 km 2 ), whereas lakes with buried water are larger (∼6–10 km 2 ). Lake area is correlated with the number of seasons sub-surface water persists. Buried lakes are relatively deep and associated with complex supraglacial channel networks. Winter stored water could be a precursor to the formation of supraglacial channels. Simulations of the insulation potential of accumulated snow and ice on the surface of lakes indicate substantial regional differences and inter-annual variability. With the possibility of inland migration of supraglacial lakes, buried lakes could be important in the evolution of ablation/percolation zone hydrology.